2009
DOI: 10.1111/j.1750-3841.2008.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fermentation Conditions on Glucosinolates, Ascorbigen, and Ascorbic Acid Content in White Cabbage (Brassica oleracea var. capitata cv. Taler) Cultivated in Different Seasons

Abstract: The content of glucosinolates (GLS), ascorbigen, and ascorbic acid in white cabbage (Brassica oleracea var. capitata cv. Taler) cultivated in different seasons (summer and winter) was determined, before and after spontaneous and starter-induced fermentation. Different salt concentrations (0.5% NaCl or 1.5% NaCl) were used for sauerkraut production. Glucoiberin, sinigrin, and glucobrassicin were dominating in raw white cabbage cultivated either in winter or summer seasons. Ascorbigen precursor, glucobrassicin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 47 publications
7
63
1
3
Order By: Relevance
“…In food matrices such as sauerkraut, however, one of the most useful methods used has been the high-performance liquid chromatography with UV detection HPLC-PAD (Martinez-Villaluenga et al 2009;Peñas et al 2010). Due to the importance of ABG bioactivity, the progress in analytical methods in food is still of scientific interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In food matrices such as sauerkraut, however, one of the most useful methods used has been the high-performance liquid chromatography with UV detection HPLC-PAD (Martinez-Villaluenga et al 2009;Peñas et al 2010). Due to the importance of ABG bioactivity, the progress in analytical methods in food is still of scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…During sauerkraut preparation, indole GLS glucobrassicin (GB) yields first an unstable isothiocyanate that further degrades with loss of S to form the intermediate indole-3-carbinol (I3C) that spontaneously reacts with L-ascorbic acid forming ABG at acid pH (Zeligs 1998). It has been reported that ABG is not present in intact plant tissues (Preobrazhenskaya et al 1993) or it is present in low quantities in just shredded cabbage because a certain amount of GB might have been hydrolysed by the endogenous myrosinase as a consequence of cell damage (Ciska and Pathak 2004;Martinez-Villaluenga et al 2009;Peñas et al 2010). ABG formation is strongly dependent on the pH and the already formed ABG remains relatively stable at pH 4-5 characteristics of fermented cabbage products (Aleksandrova et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one study observed fermentationconditiondependent changes in the GSL content of white cabbages harvested by season (Villaluenga et al, 2009).…”
Section: Changes In Gsl Levels In Chinese Cabbagementioning
confidence: 99%
“…The selection criteria for lactic acid bacteria used in vegetable and vegetable juice fermentations has been summarised in 1993 by Buckenhüskes (Buckenhüskes 1993, Daeschel et al 1987, Lücke et al 1990, Buckenhüskes 1992. Daeschel and Fleming (1984) have also discussed the selection of lactic acid bacteria to be used in vegetable fermentations and the use of starters has further been studied in several works (Frank 1973, Flem-ing et al 1985, Buckenhüskes et al 1986, Delclos 1992, Harris et al 1992, Breidt et al 1993, Breidt et al 1995, Halasz et al 1999, Savard et al 2000, Gardner et al 2001, Tolonen et al 2002, Wiander and Ryhänen 2005, Johanningsmeier et al 2007, Wiander and Ryhänen 2007, Wiander and Ryhänen 2008, Martinez-Villaluenga et al 2009, Penas et al 2010. Commercial starters are available on the market, but they are not widely used in sauerkraut and sauerkraut juice fermentations.…”
Section: Introductionmentioning
confidence: 99%